Challenges and opportunities in the management of cardiovascular diseases (Sciences of Phytochemistry, 2022)
In the 21st century, cardiovascular diseases (CVDs) constitute the leading cause of death. It is difficult for potential CVD therapies to be successful since CVDs cannot be effectively or cheaply treated with existing therapy. To formulate and transport therapeutically active molecules to treat a variety of ailments, innovative drug delivery carrier systems have emerged as an efficient method. Their applications have a potential role in routine drug discovery. Heart failure has been studied using a variety of novel treatment approaches, such as cell transplantation, gene transfer or therapy, cytokines, or other small molecules. This review briefly highlights key points in the management of CVDs.